Penanganan Dampak Abu Vulkanik Letusan Gunung Lewotobi Terhadap Operasi Penerbangan - Fitria, Rosi; Asep Adang Supriyadi; Syachrul Arief; Dangan Waluyo (UNIB Press, 2025)
Volcanic ash poses a serious threat to aviation due to its abrasive nature and its tendency to melt at high temperatures, as evidenced by the 1982 British Airways incident at Mount Galunggung. The eruption of Mount Lewotobi from November 7 to 18, 2024, caused ash dispersion that disrupted operations at 13 airports, resulting in the cancellation of hundreds of domestic flights and dozens of international flights. This study employs a qualitative descriptive method, utilizing secondary data, to evaluate how the impacts of the eruption on aviation were managed. The results show that the response was carried out effectively in accordance with Regulation No. PM 95 of 2018, with no serious incidents reported. This was achieved through coordinated dissemination of VONA, VAA, and SIGMET reports, as well as the issuance of ASHTAM and NOTAM. Recommendations are focused on enhancing coordination, strengthening monitoring, and updating aviation operational procedures.